Supporting Interventions to Reduce Household Greenhouse Gas Emissions: A Transdisciplinary Role-Playing Game Development. (June 2019) - Agusdinata, Datu Buyung; Lukosch, Heide
Background . Designing interventions for conserving thefood, energy, and water nexus at household level poses a significant challenge due to the complex interplay betweenhuman behaviors, technologies, and policies . Games show potential to increaseawareness for environmental issues and influence behaviors towards more sustainable practices. Aim . By bringing together scientists and practitioners in the game design process, atransdisciplinary (TD) approach is seen as a promising way to integrate available knowledge and establish ownership of the problem and solution options. Few gaming literature, however, looked at combining the two approaches in addressing resource conservation issues. Method . We present a systematic account of the TD approach process of developing arole-playing game (RPG) - called HomeRUN (Role-play for Understanding Nexus). Results . We documented our experiences in terms of challenges as well as the benefits of the TD approach.Interacting disciplines in this process include psychology, economics, engineering, climate, sociology, and computer science. Inputs from each discipline combined with feedback from social actors that include city government, utility companies, and community members facilitated continuous improvements of the RPG design.